2013
DOI: 10.2174/1381612811319170012
|View full text |Cite
|
Sign up to set email alerts
|

Non-ACE Pathway-induced Angiotensin II Production

Abstract: For the past century, the renin-angiotensin system (RAS) has been recognized as one of the major blood pressure-regulating systems. Angiotensin II (Ang II) is the final physiologically active product of RAS, and it works not only as a strong vasopressor but also as a promotor of tissue remodeling in various organs such as heart, arteries, and kidneys. RAS is the predominant pathway of Ang II formation in human plasma, but not in the tissues. There are several alternative pathways producing angiotensin II in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 0 publications
2
36
0
4
Order By: Relevance
“…Paradoxically, despite reduced ACE activity in ANG-(1-7)-treated right ventricles, ANG-II level remained high (data not shown), which suggests that other enzymes or pathways besides ACE may be involved in the formation of ANG-II. One such candidate is chymase, which has been detected in cardiac and vascular tissues (29). Consistent with previous results of a model of pulmonary fibrosis induced by bleomycin (23), we first demonstrated that ANG-(1-7) treatment downregulated the level of AT 1 receptor and upregulated that of AT 2 receptor in diabetic RV tissues.…”
Section: Discussionsupporting
confidence: 90%
“…Paradoxically, despite reduced ACE activity in ANG-(1-7)-treated right ventricles, ANG-II level remained high (data not shown), which suggests that other enzymes or pathways besides ACE may be involved in the formation of ANG-II. One such candidate is chymase, which has been detected in cardiac and vascular tissues (29). Consistent with previous results of a model of pulmonary fibrosis induced by bleomycin (23), we first demonstrated that ANG-(1-7) treatment downregulated the level of AT 1 receptor and upregulated that of AT 2 receptor in diabetic RV tissues.…”
Section: Discussionsupporting
confidence: 90%
“…Крім нирок настільки висока актив-ність локальної РААС виявлена при ЦД у серці і ендотелії судин. Надмірне утворення АТ II в нирках веде до внутрішньоклубочкової гіпертензії, потім до склерозу і фіброзу ниркової тканини, у серці -до ремоделювання міокарду, в судинах сприяє розвитку атеросклерозу [12]. Дослідження останніх років показали, що гіперактивність РААС грає важ-ливу роль в розвитку інсулінорезистентності (ІР), що в свою чергу може привести і до ЦД 2 типу [9].…”
Section: Elenaltrawneh@gmailcomunclassified
“…Компоненти локаль-ної РААС виявлені як в екзокринних протоках, так і в b-клітинах острівців підшлункової залози. Це до-зволило пояснити блокуючу дію АТ II на секрецію інсуліну і посилення ІР периферійних тканин при його надмірній секреції [2,12].…”
Section: Elenaltrawneh@gmailcomunclassified
“…This further bolsters the presence of an Angiotensin Converging Enzymes (ACE)-independent pathway in angiotensin-II formation. In the last two decades, the activity of alternate pathways mediating the conversion of angiotensin-I to angiotensin-II were discovered [16], challenging renin-angiotensin-aldosterone system as the sole pathway. The raveling of an alternate pathway was discovered by Cornish and colleagues in 1978, who reported the existence of a possible alternate pathway in angiotensin-II formation in animal models [12].…”
Section: Introductionmentioning
confidence: 99%